2019
DOI: 10.7150/jca.36289
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and The Safety of Ultrasound-guided Ablation Therapy for Treating Papillary Thyroid Microcarcinoma

Abstract: The prevalence of papillary thyroid microcarcinoma (PTMC) increases rapidly all around the world, but the management of PTMC hasn't reached a consensus. Recently, ultrasound-guided (US-guided) ablation therapy was introduced as a feasible treatment for low-risk PTMC. The clinical application of US-guided ablation therapy needs doctors' effort to investigate the efficacy and the safety of US-guided ablation in treating PTMC carefully. Although the present evidence showed some limitations, such as short-term stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Large blood vessels should be avoided in advance. (4) Operators should be proficient in basic techniques of ablation, such as the moving shot technique, the multiple overlapping shot technique, the hydrodissection technique, and leveraged pry-off method (14)(15)(16)(17). Insufficient experience or unskilled operation can easily lead to failure of treatment, and even the risk of uncontrollable bleeding that requires conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Large blood vessels should be avoided in advance. (4) Operators should be proficient in basic techniques of ablation, such as the moving shot technique, the multiple overlapping shot technique, the hydrodissection technique, and leveraged pry-off method (14)(15)(16)(17). Insufficient experience or unskilled operation can easily lead to failure of treatment, and even the risk of uncontrollable bleeding that requires conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…By retrieving pertinent literatures, we found that there has been one case report of a patient with thyroid cancer presenting with TIO and bone metastasis. 17,18 Although this patient had a history of papillary thyroid carcinoma, testing indicated that the patient's TIO and bone metastases were due to a phosphaturic mesenchymal tumour. 19 Genetic mechanism by which tumours express FGF-23 is not well known.…”
Section: Discussionmentioning
confidence: 97%
“…Papillary thyroid microcarcinoma (PTMC) with a tumor diameter ≤1 cm occurs in >50% of all new-onset thyroid cancer types, and its incidence has been increasing rapidly over the last several decades worldwide ( 9 , 10 ). Clinically, numerous studies have reported that PTMC had a favorable prognosis in the majority of cases following surgical interventions ( 11 13 ). However, PTMC tumor growth is usually slow and certain patients developed clinically problematic tumor growth after multiple years of observation ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%